Obesity Is Associated With Increased Complications After Operative Management of End-Stage Ankle Arthritis. (August 2015) - Werner, Brian C.; Burrus, M. Tyrrell; Looney, Austin M.; Park, Joseph S.; Perumal, Venkat; Cooper, M. Truitt
Background: Total ankle arthroplasty (TAA) and ankle arthrodesis (AA) are two operative options for the management of end-stage ankle arthritis that has failed conservative interventions. Obesity is associated with a greater incidence of musculoskeletal disease, particularly osteoarthritis of the weight-bearing joints, including the ankle. The objective of the present study was to use a national database to examine the association between obesity and postoperative complications after TAA and AA. Methods: The PearlDiver database was queried for patients undergoing AA and TAA using International Classification of Diseases, 9th Revision (ICD-9) procedure codes. Patients were divided into obese (body mass index ≥30 kg/m 2 ) and nonobese (body mass index <30 kg/m 2 ) cohorts using ICD-9 codes for body mass index and obesity. Complications within 90 days postoperatively were assessed using ICD-9 and Current Procedural Terminology (CPT) codes. Results: 23, 029 patients were identified from 2005 to 2011, including 5361 with TAA and 17, 668 with AA. Obese TAA patients had a significantly increased risk of 90-day major, minor, local, systemic, venous thromboembolic, infectious, and medical complications compared with nonobese patients. The incidence of revision TAA was also significantly higher in obese patients compared with nonobese patients. Findings were similar for AA, as all types of complications were significantly higher in obese patients compared with nonobese patients. Conclusion: Obesity was associated with significantly increased rates of all complications after both TAA and AA. The cause of this association was likely multifactorial, including increased rates of medical comorbidities, intraoperative factors, and larger soft tissue envelopes. Level of Evidence: Level III, comparative series.